2022
DOI: 10.3390/antiox11112083
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase as a Potential Biomarker of Acute-Myocardial-Infarction-Induced Depression and Suppression of the Innate Immune System

Abstract: While myeloperoxidase (MPO) serves as an indicator of both neutrophil and innate-immune-system function, the potential suppression of the innate immune system in patients with acute myocardial infarction (AMI)-induced depression might be evidenced by a decrease in MPO serum levels. The aim of this prospective study was to (1) determine whether serum concentrations of MPO vary immediately and 6 months after AMI and (2) to investigate whether MPO concentrations at the time of the AMI are significant predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Research reported that increased level of SHMT2 [625] and MPO (myeloperoxidase) [640] are related to pulmonary hypertension, as a novel target for pulmonary hypertension diagnosis and treatment. A recent study found that the S100A9 [239], FKBP5 [240], SNCA (synuclein alpha) [221] and MPO (myeloperoxidase) [256] are crucial for the progression of depression and anxiety. Regulation of MPO (myeloperoxidase) [1445] and CD177 [1440] levels might be a novel treatment option against polycythemia.…”
Section: Discussionmentioning
confidence: 99%
“…Research reported that increased level of SHMT2 [625] and MPO (myeloperoxidase) [640] are related to pulmonary hypertension, as a novel target for pulmonary hypertension diagnosis and treatment. A recent study found that the S100A9 [239], FKBP5 [240], SNCA (synuclein alpha) [221] and MPO (myeloperoxidase) [256] are crucial for the progression of depression and anxiety. Regulation of MPO (myeloperoxidase) [1445] and CD177 [1440] levels might be a novel treatment option against polycythemia.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum MPO has been described in multiple sclerosis 49 , depression 50 , and schizophrenia 51 . Interestingly, Baranyi et al (2022) 52 described lower MPO levels in patients with acute myocardial infarction (AMI) induced depression compared to AMI patients that did not develop depression. This suggests that there may be an interaction occurring between inflammatory and neuropsychiatric states with regards to MPO serum levels, but further research is needed.…”
Section: Discussionmentioning
confidence: 99%